The Islamic empire - Nardo, Don; Gale Group (Detroit Lucent Books, 2011)
Provides an overview of important historical events or periods in world history. This volume focuses on the history of the Islamic Empire.
ch 1. Muhammad and his struggles--Ch 2. The early Muslim conquests--Ch 3. Islam rocked by civil strife--Ch 4. A new burst of expansion--Ch 5. Baghdad and its challengers--Ch 6. Islamic culture's golden age.
Electronic reproduction.
Keywords: Islamic civilization; Islamic Empire